광중합형 복합레진 충전 급여에 따른 소요재정 추계 - 류재인; Jae-in Ryu; 정세환; Se-hwan Jung; 한동헌; Dong-hun Han; 이새롬; Sae-rom Lee; 전지은; Ji-eun Jeon (대한구강보건학회지, 2019)
Objectives: This study aimed to estimate the financial budget of light-curing composite resin fillings based on the expanded coverage of the National Health Insurance Service (NHIS), called “Moon Care.” Methods: The estimated population with dental caries and the amount of light-curing composite resins used were determined. The fees for the resin fillings per tooth were considered for the calculations. The expected budget for the next five years for children and adolescents aged 5-12 and 5-19 years were calculated. Results: During the first year of the coverage, the budget for children and adolescents aged <19 years was estimated to be 201.8 billion South Korean won (5-9 years, 17.9 billion South Korean won; 10-14 years, 76.6 billion South Korean won; and 15-19 years, 107.3 billion South Korean won). The total budget for the next five years for children and adolescents aged <19 years was estimated at 946.4 billion South Korean won. Likewise, the budget for children aged <12 years during the first year of the coverage was estimated at 63.9 billion South Korean won (5-9 years, 17.9 billion South Korean won and 10-12 years, 46 billion South Korean won), and the total budget for the next five years was estimated at 315.9 billion South Korean won. Conclusions: Government healthcare plans should be established based on treatment needs and financial estimations. All the items in the NHIS, including the light-curing composite resin filling, should be considered based on their contribution to oral health promotion. Furthermore, in the long term, the coverage for preventive health services should be included in the health insurance.